PENGARUH CELEBRITY ENDORSER, ASOSIASI MEREK, KEPERIBADAIAN MEREK DAN KARAKTERISTIK PRODUK TERHADAP INTENS PEMBELIAN PRODUK KOPI DI JAKARTA BARAT - Kurniati W Andani, Hannes Widjaya, Chandra Saputra, (Jurnal Ekonomi, 2015)
Perceptions of the product can be built the company by providing information on the product, and the best way in the delivery of information is the promotion. One way of promotion of the most rising concern of many companies in introducing their products is  through  advertising.  The  purpose of  this  study was  to  determine  the  influence  of celebrity  endorsers, brand association,  brand  personalities  and  characteristics  of  the product to the intention of purchase. Sample selection methods by using a simple random sampling. Data obtained through questionnaires of 125 respondents in West Jakarta as a sample of researchers. Analyses were performed using multiple regression analysis. The results  showed  that  of  the  four  independent variables,  celebrity  endorser,  brand association, brand personality and product characteristics significantly influence purchase intention simultaneously, while celebrity endorser does not significantly affect the intense partial purchase.